1998
DOI: 10.1017/s1047951100006806
|View full text |Cite
|
Sign up to set email alerts
|

Growing up with congenital heart disease: the dilemmas of adolescents and young adults

Abstract: Advances in diagnosis, medical management and surgical intervention have improved the longevity and quality of life for children with congenital heart disease. Despite this, research studies specifically examining the psychosocial concerns of adolescents and young adults with congenital heart disease are few. To explore the subjective experiences and dilemmas of this population during the transition from adolescence to young adulthood, we interviewed, using a semi-structured protocol, a convenience sample of n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
79
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(85 citation statements)
references
References 15 publications
6
79
0
Order By: Relevance
“…Most studies of this type survey parents, and few investigators have relied on direct responses from children with congenital heart defects. 14 Guyatt et al 15 noted that parents of children aged 11 years or older provided little information regarding their child's quality of life beyond that obtained directly from the child.…”
Section: Discussionmentioning
confidence: 99%
“…Most studies of this type survey parents, and few investigators have relied on direct responses from children with congenital heart defects. 14 Guyatt et al 15 noted that parents of children aged 11 years or older provided little information regarding their child's quality of life beyond that obtained directly from the child.…”
Section: Discussionmentioning
confidence: 99%
“…Similar findings were noted in the recent Kennedy report. 10a Studies which have consulted young people directly [11][12][13] have also suggested that they had needs for rehabilitation that were not met. A recent survey of all centres for paediatric cardiology in the United Kingdom indicated that, whilst the health professionals agreed that rehabilitation was required, only one centre reported having a formal programme serving this purpose.…”
Section: O Ver the Last Decade There Has Been Anmentioning
confidence: 99%
“…One recommendation was that "all health professionals need to take a holistic approach to caring for children, including consulting them about their own needs, since their views are not necessarily the same as adult proxies". 16 Few studies, with some exceptions, 17,18 have directly sought the views of young people with congenital cardiac disease. The findings of studies that have consulted young people suggest that they had needs for rehabilitation that were not met.…”
mentioning
confidence: 99%